Analisis Pengaruh Perputaran Modal Kerja Terhadap Profitabilitas Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Santika, Epi; Asrida, Wa; Sipakoly, Selly; Hariyanti, Dwi; Hariyati, Tri Retno (Journal of Applied Accounting, 2025)
Abstract This research was conducted to determine the effect of working capital turnover on profitability at PT. Mayora Indah Tbk. This study uses simple linear regression analysis method to ascertain the direction of the relationship between independent variables and dependent variables, whether it has a positive or negative relationship, and to predict the value of the dependent variable when the value of the independent variable experiences an increase or decrease using the formula Y = a + bX. The results of this study, based on simple linear regression testing, indicate that working capital turnover negatively affects profitability, as well as the t-test, indicating that working capital turnover does not have a significant effect on profitability. Keywords: Working Capital Turnover, Profitability